2005
DOI: 10.1146/annurev.nutr.25.121304.131724
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Localization, and Noncarboxylase Roles of Biotin

Abstract: Evidence is emerging that biotin participates in processes other than classical carboxylation reactions. Specifically, novel roles for biotin in cell signaling, gene expression, and chromatin structure have been identified in recent years. Human cells accumulate biotin by using both the sodium-dependent multivitamin transporter and monocarboxylate transporter 1. These transporters and other biotin-binding proteins partition biotin to compartments involved in biotin signaling: cytoplasm, mitochondria, and nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 168 publications
(123 citation statements)
references
References 144 publications
(196 reference statements)
2
118
1
2
Order By: Relevance
“…However, it remains uncertain how the same enzyme may act as a biotinyl transferase in one case and as a debiotinylase in another. It has been proposed that regulation of biotinidase is achieved by interactions with chromatin-associated proteins, posttranslational modifications and alternative splicing, and substrate availability [17]. Note that we have detected biotinidase in human cell nuclei [11], whereas other groups suggest that biotinidase is primarily an extranuclear protein [23].…”
Section: Introductioncontrasting
confidence: 50%
See 1 more Smart Citation
“…However, it remains uncertain how the same enzyme may act as a biotinyl transferase in one case and as a debiotinylase in another. It has been proposed that regulation of biotinidase is achieved by interactions with chromatin-associated proteins, posttranslational modifications and alternative splicing, and substrate availability [17]. Note that we have detected biotinidase in human cell nuclei [11], whereas other groups suggest that biotinidase is primarily an extranuclear protein [23].…”
Section: Introductioncontrasting
confidence: 50%
“…Evidence that biotinylation of histones plays a role in cell proliferation [10], cellular response to DNA damage [15], mitotic condensation of chromatin [16] and heterochromatin structures and gene silencing has been provided (Camporeale et al, submitted for publication). Collectively, the binding of biotin to histones participates in epigenetic events that are crucial for maintaining genomic stability and chromatin structure [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest additional roles for this vitamin in cell signaling, gene expression, and chromatin structure in mammalian cells (reviewed in ref. 1). Biotin is synthesized by many bacteria, certain archaea, fungi, and plants (reviewed in ref.…”
Section: B Iotin (Vitamin H) Is An Essential Cofactor In Carboxylationmentioning
confidence: 99%
“…26 The detection of HCS in cell nuclei and the HCS-catalyzed biotinylation of histones in vitro suggested that HCS might be responsible for biotin attachment to histones in vivo. 20 However, the recent finding of Streaker and Beckett 19 that the bio-5 0 -AMP product of BirA was sufficient, in the absence of enzyme, to produce biotin transfer to BCCP87 led us to examine the behavior of HCS and BirA toward histones, that is, whether the rate and specificity of biotin addition to histones depended on the BPL or whether the role of the biotin ligase might be limited to the generation of bio-5 0 -AMP.…”
Section: Discussionmentioning
confidence: 99%